A-V malformation of nose: A rare challenging case - Chaudhuri, Gaurab Ranjan; Guha, Ruma; Hansda, Rajesh; Bandyopadhyay, Soumendra Nath (Asian Journal of Medical Sciences, 2017)
Congenital A-V malformations of head-neck region are extremely uncommon lesions encountered in clinical practice. They may lead to a wide array of clinical effects from cosmetic disfigurement and recurrent life threatening haemorrhage to cardiac failure. Treatment of these lesions pose a challenge to reconstructive surgeons due to their extreme vascularity, high incidence of recurrence and involvement of adjacent vascular channels. The case presented here is a congenital A-V malformation treated successfully by thorough surgical excision and reconstruction by a well vascularised flap. Asian Journal of Medical Sciences Vol.8(1) 2017 94-97